Pandemic Influenza and Jail Facilities and Populations - Maruschak, Laura M. (Am J Public Health, 2009)
Persons processed into and through jail facilities in the United States may be particularly vulnerable during an influenza pandemic. Among other concerns, public health and corrections officials need to consider flow issues, the high turnover and transitions between jails and the community, and the decentralized organization of jails. In this article, we examine some of the unique challenges jail facilities may face during an influenza pandemic and discuss issues that should be addressed to reduce the spread of illness and lessen the impact of an influenza pandemic on the jail population and their surrounding communities.